2015
DOI: 10.1128/jb.00034-15
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the Membrane Nuclease Gene (MBOVPG45_0215) of Mycoplasma bovis Greatly Reduces Cellular Nuclease Activity

Abstract: Although the complete genome sequences of three strains of Mycoplasma bovis are available, few studies have examined gene function in this important pathogen. Mycoplasmas lack the biosynthetic machinery for the de novo synthesis of nucleic acid precursors, so nucleases are likely to be essential for them to acquire nucleotide precursors. Three putative membrane nucleases have been annotated in the genome of M. bovis strain PG45, MBOVPG45_0089 and MBOVPG45_0310, both of which have the thermonuclease (TNASE_3) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 45 publications
0
37
0
Order By: Relevance
“…Zymogram analysis involves inhibition of nuclease activity by sodium dodecylsulfate (SDS) and renaturation following SDS removal by diffusion [ 10 ]. Briefly, total cellular proteins of M. bovis HB0801, rMbovNase, or rMbovNase Δ181–342 protein were mixed with SDS loading buffer, heated to 100 °C for 10 min, and loaded onto 12% SDS-PAGE gels saturated in advance with herring sperm DNA (160 μg·mL −1 ; Sigma–Aldrich, St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zymogram analysis involves inhibition of nuclease activity by sodium dodecylsulfate (SDS) and renaturation following SDS removal by diffusion [ 10 ]. Briefly, total cellular proteins of M. bovis HB0801, rMbovNase, or rMbovNase Δ181–342 protein were mixed with SDS loading buffer, heated to 100 °C for 10 min, and loaded onto 12% SDS-PAGE gels saturated in advance with herring sperm DNA (160 μg·mL −1 ; Sigma–Aldrich, St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, several nucleases have been implicated in mycoplasma-mediated host pathogenicity and cytotoxicity [ 7 , 8 , 9 ]. Based on the sequence alignment, there is a highly conserved region named TNASE_3 belonging to micrococcal nuclease (thermonuclease) COG1525 [ 10 ]. The conserved region has several catalytic sites involved in the nuclease activity and binding of calcium ions [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple predicted nuclease genes are present in the M. bovis genome, including three in the PG45 type strain. In vitro studies using transposon mutants disclosed MBOVPG45_0215 as exhibiting the majority of nuclease activity for the DNA substrates tested (Sharma, Tivendale, Markham, & Browning, ). A recombinant form of a second nuclease MBOV_RS02825 (equivalent to MBOVPG45_0310) was shown to degrade the DNA component of NETs and to induce apoptosis of macrophages (Zhang et al., ).…”
Section: The Causative Organismmentioning
confidence: 99%
“…The results suggested that hydrolytic activity or the expression level of Mpn133 may be apparently lower than that of Mpn491, and it might be possible that Mpn133 is less important for the resistance of M. pneumoniae to NETs‐mediated killing than Mpn491. Meanwhile, another study reported that Mpn491 possesses glutamic acid‐lysine‐serine region‐like amino‐acid sequence between residues 175 and 218 (Sharma, Tivendale, Markham, & Browning, ), raising a possibility that the nuclease might also exert a cytotoxic activity toward mammalian cells. Further research is required to fully elucidate the additional function of the nuclease.…”
Section: Discussionmentioning
confidence: 99%